A contemporary understanding of organizational climate in healthcare setting: A concept analysis. Issue 1 (5th October 2020) - Sein Myint, Nwe Ni; Kunaviktikul, Wipada; Stark, Azadeh
Abstract: Aim: The overarching objective of this report is to provide an updated definition of the concept of organizational climate and to strengthen its operational application. Background: Organizational climate is one of the major contributing factors to the exodus of the nursing workforce from the profession. Extensive research has addressed the impact of "organizational climate" on the nursing workforce; yet variations in the interpretation of the concept calls for an updated definition. Design: Walker and Avant's strategy was implemented. Data Source: Data were compiled from Medline and CINAHL, Google search engine, and book chapters. Review Method: A comprehensive and detailed review of the literature was performed. Nineteen historic publications (1939–2012) and 39 healthcare‐related publications (2013–2018) were included in the final review. Results: The climate of an organization reflects a set of core values and behaviors that can be used to implement evidence‐based leadership and management within the context of the 21st century. We have revised the definition of organizational climate to capture this context. Conclusion: The perception of a supportive and constructive climate in an organization propels the workforce, independent of ethnic or personal background, to a higher level of productivity and encourages loyalty and workforce stability.